Mental Health Care Goes Online: Practitioners' Experiences of Providing Mental Health Care During the COVID-19 Pandemic - Feijt, Milou; de Kort, Yvonne; Bongers, Inge; Bierbooms, Joyce; Westerink, Joyce; IJsselsteijn, Wijnand (Cyberpsychology, behavior and social networking, 2020)
The outbreak of the COVID-19 pandemic has necessitated sudden and radical changes in mental health care delivery, as strict social distancing and lockdown measures were imposed in the early phases of the pandemic. Almost overnight, practitioners were forced to transfer their face-to-face care practice to online means. To understand the implications of this drastic change for mental health care, and to improve the online care offerings, an online qualitative survey was held among mental health care professionals in Netherlands ( = 51). Our findings indicate that technological and usability problems pose a significant challenge, as do difficulties to establish rapport with clients. Moreover, not all mental health issues and treatment forms are equally amenable to online interaction. In contrast, in many instances, practitioners were positive about the effectiveness of treatment, and reported flexibility, a lower threshold for contact, and lack of travel time as advantages. Their most prominent needs concern better technological, organizational, and logistical support. It is critical that these needs are acted upon by institutions and governments. In addition, current results inform future research on the improvement of e-mental health technologies.